The Relationship Between Coding Knowledge and Genitorinary Diagnosis Coding Accuracy: A Cross-Sectional Study at Drs. H. Amri Tambunan Hospital - Selviani Damayanti Br. Sipayung; Pestaria Saragih; Pomarida Simbolon (Pancasakti Journal Of Public Health Science And Research, 2025)
The accuracy of the genitourinary diagnosis code is considered precise and accurate and in accordance with ICD 10. The inaccuracy of the diagnosis code is influenced by the lack of knowledge of the coder to code specifically in genitourinary cases in medical records. Inaccurate coding impacts the quality of medical record data, financing claims, clinical decision-making in disease coding. The purpose of this study was to identify the relationship between coder knowledge and the accuracy of genitourinary diagnosis codes. The study design used a cross-sectional analytical approach. The study sample consisted of 35 coders, medical record officers, and polyclinic registration officers using a total sampling technique. The instruments used were a coder knowledge questionnaire and a genitourinary diagnosis code accuracy checklist. Data analysis used a chi-square test. The results of the study obtained high coder knowledge in 18 people (51.4%), and the accuracy of genitourinary diagnosis was correct in 25 people (71.4%). The Chi-square test results showed a p-value of 0.003 (p <0.05). This indicates a significant relationship between coder knowledge and the accuracy of genitourinary diagnosis codes. Hospitals are expected to conduct disease coding training to improve the coding process, which is consistent with claims.